2023
DOI: 10.3892/ijmm.2023.5321
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin alleviates lipopolysaccharide‑induced acute lung injury by inhibiting ferroptosis via the Sirt1/Nrf2/Gpx4 pathway

Shihua Deng,
Jin Li,
Li Li
et al.

Abstract: Acute lung injury (ALI) causes high morbidity and mortality rates in critically ill patients, and there are currently no effective therapeutic drugs. Ferroptosis is a newly discovered mode of regulated cell death that contributes to the progression of ALI. Quercetin possesses anti-inflammatory and antioxidant properties. However, whether quercetin can protect against lipopolysaccharide (LPS)-induced ALI by inhibiting ferroptosis and its underlying mechanisms remains unclear. The present study evaluated the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…The most common treatments for acute lung injury are glucocorticoids, which come with serious side effects. Ferroptosis inhibition is seen as a new potential target for the development of new therapeutics [ 130 , 131 , 132 ]. Chicoric acid was able to alleviate LPS-induced lung injury in mice thanks to its anti-inflammatory and anti-oxidative activities.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common treatments for acute lung injury are glucocorticoids, which come with serious side effects. Ferroptosis inhibition is seen as a new potential target for the development of new therapeutics [ 130 , 131 , 132 ]. Chicoric acid was able to alleviate LPS-induced lung injury in mice thanks to its anti-inflammatory and anti-oxidative activities.…”
Section: Resultsmentioning
confidence: 99%
“…Ferulic acid and Naringenin are other polyphenolics with a proven ability to alleviate acute lung injury through activation of the Nrf2/HO-1 signaling pathway and subsequent inhibition of ferroptosis [ 134 , 135 ]. Also, quercetin alleviated lung injury through ferroptosis inhibition by activating the Sirt1/Nrf2/GPX4 pathway [ 130 ].…”
Section: Resultsmentioning
confidence: 99%
“…But the targets that through them ferroptosis is inhibited are different from those in cancer cells. In acute lung injury and Parkinson's disease, the main mechanism is attributed to the activation of NRF2 signaling (Deng et al, 2023;Lin et al, 2022), while in asthma and spinal cord injury, these effects are exerted through suppressing the immune response and, Id2/transferrin pathway, respectively (Wang, Li, Wang, Chen, & Goh, 2023;Wang, Li, Wang, Zhu, Liu, et al, 2023;Wang, Lin, Huang, Liu, Chen, et al, 2023;Wang, Liu, Li, Zha, Chen, et al, 2023;Wang, Shen, Lian, Deng, Qu, et al, 2023;Wang, Tan, Zhang, Wu, & Shi, 2023;Wang, Wan, Peng, Zhao, Bai, & Hu, 2023). This dual role, modulating NRF2 signaling, suppressing immune response, or affecting specific pathways, emphasizes the need for a nuanced understanding of quercetin's effects in different contexts.…”
Section: Quercetinmentioning
confidence: 99%
“…122 Deng et al found that quercetin (40 mg/kg) upregulated the expression of antioxidant enzymes such as Sirt1, Nrf2, GPx4, SOD, and GSH in a mouse model of lipopolysaccharide-induced acute lung injury, which in turn mitigated the lung injury. 123 Another study showed that gallic acid, proanthocyanidins, ellagic acid, and tannic acid had a significant therapeutic effect on dextran-sulfate-sodium-salt (DSS)-induced ulcerative colitis (UC) in C57BL/6 mice. All polyphenols (100 mg/kg) improved the symptoms of UC in mice and the antioxidant capacity of polyphenols correlated with the number of phenolic hydroxyl groups and the structure of the o-phenolic group.…”
Section: Fpps Classification and Antioxidant Propertiesmentioning
confidence: 99%